Corrosion Acceleration of Printed Circuit Boards With an Immersion Silver Layer Exposed to Bacillus cereus in an Aerobic Medium - Hu, Yuting; Xiao, Kui; Zhang, Dawei; Yi, Pan; Xiong, Ruilin; Dong, Chaofang; Wu, Jusheng; Li, Xiaogang (Frontiers in Microbiology, 2019)
In this research, the corrosion behavior of printed circuit boards with an immersion silver layer (PCB-ImAg) exposed to Bacillus cereus bacteria in Luria-Bertani broth was investigated. The growth test demonstrated that B. cereus had a high copper tolerance. Analysis of surface and cross-sectional view of the samples after immersion test indicated that metabolites produced by B. cereus accelerated the microporous corrosion of PCB-ImAg, and the biofilm that adhered to the surface led to oxygen concentration corrosion. Electrochemical impedance spectroscopy tests confirmed that the microbiologically influenced corrosion of PCB-ImAg was related to the biofilm formation and metabolism.